2014
DOI: 10.1063/1.4871730
|View full text |Cite
|
Sign up to set email alerts
|

Efficient multi-keV x-ray source generated by nanosecond laser pulse irradiated multi-layer thin foils target

Abstract: A new target configuration is proposed to generate efficient multi-keV x-ray source using multiple thin foils as x-ray emitters. The target was constructed with several layers of thin foils, which were placed with a specific, optimized spacing. The thin foils are burned though one by one by a nanosecond-long laser pulse, which produced a very large, hot, underdense plasma. One-dimensional radiation hydrodynamic simulations show that the emission region and the multi-keV x-ray flux generated by multi-layer thin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Owing to the low average electron density over the wide space between the two foils, the electron internal energy is enhanced. However, the x-ray radiation reduces noticeably because the x-ray emissivity, which is proportional to the square of electron density, decrease significantly [35]. Finally, the x-ray CE is even smaller than that of the normal target for very large distance ( = d 10 000 2 μm).…”
Section: Influences Of Target Geometry Parameters On X-ray Cementioning
confidence: 96%
See 1 more Smart Citation
“…Owing to the low average electron density over the wide space between the two foils, the electron internal energy is enhanced. However, the x-ray radiation reduces noticeably because the x-ray emissivity, which is proportional to the square of electron density, decrease significantly [35]. Finally, the x-ray CE is even smaller than that of the normal target for very large distance ( = d 10 000 2 μm).…”
Section: Influences Of Target Geometry Parameters On X-ray Cementioning
confidence: 96%
“…laser parameters and foil thickness should be chosen carefully, otherwise the x-ray emission can only be enhanced by a small margin, since this scheme changes the target ablation process from one-sided expansion (thick foil) to two-sided expansion (pre-exploded thin foil). Rarefaction waves coming from two sides of the thin foil will destroy the emission region quickly [35]. To depress the rarefaction wave of the hot coronal plasma generated from the solid targets and enhance the laser to x-ray CE, new approaches or solutions are required.…”
Section: Enhancement Of Laser To X-ray Conversion By a Double-foil Go...mentioning
confidence: 99%
“…The conversion of lasers into X-rays is an important topic in the field of laser plasmas. For decades, many scientists paid their attentions to acquire X-rays for radiography in inertial confinement fusion (ICF) experiments [1][2][3][4] and medical examinations [5,6] , whereas others devoted to develop quality soft X-rays source for lithography [7][8][9][10] . Soft X-rays and extreme ultraviolets (EUV) from laser plasmas are supposed the mainly solution for the future photolithography technology [11] .…”
Section: Introductionmentioning
confidence: 99%
“…It is shown that mixed, multilayer and surface-structured targets can be used to increase the laser energy absorption. For example, high-Z mixture targets [27], porous or foamlike targets [28][29][30][31], multilayer targets [32,33], nanowire arrays [34][35][36], gratings [37][38][39] and doped aerogel targets [40,41]. In this context, investigations conducted on low density structured materials have shown that foam-attached targets or multilayer targets consisting in a solid substrate coated with a low-density layer offer significant enhancement of laser energy absorption and electron heating leading to higher conversion efficiency of laser energy into x-rays or energetic particles [29-31, 42, 43].…”
Section: Introductionmentioning
confidence: 99%